THE IMPACT OF THE USE MEDIA AUDIO VISUAL ON LEARNING OUTCOMES IN ELEMANTARY SCHOOL - Syaiful Bahri; Riki Saputra; Rahmi Rahmi (Universitas Islam Negeri Imam Bonjol Padang, 2022)
This study aims to describe and analyze the impact of using visual and audiovisual media on student learning outcomes. This research took place at the State Elementary School 10 Ulakan Tapakis, Padang Pariaman, West Sumatra, Indonesia. This type of research is qualitative by using data collection instruments such as observation, interviews, and documentation. The data obtained is then analyzed and grouped according to its designation starting from data presentation, data reduction, and conclusions. The results of this study indicate that student learning outcomes tend to increase compared to previous years' learning outcomes. This can be interpreted that the achievement of these results is quite significantly increased because it is driven by the growth of focus and motivation of students to learn because it is mediated by visual and audiovisual media in an interesting way.